The use of ISO standards in the organization of environmental managemement systems - Krekoten, Roman; Salavor, Oksana; Nychyk, Oksana (My University, 2013)
Considered European environmental standards, allowing the work to organize services of environmental management in enterprises. Розглянуто європейські екологічні стандарти, що дозволяють у організувати роботу служб екологічного менеджменту на підприємствах.
Keywords: екологічні стандарти; environmental management; екологічний менеджмент; environmental standards; кафедра екології та екоменеджменту